Meneroka pengalaman dan strategi daya tindak yang digunakan oleh remaja yang mengalami kelumpuhan fizikal (bukan semulajadi) - Kho, Soo Chin (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study is qualitative research and aimed to explore the experiences and coping strategies among the physical disability adolescent (not natural born). The research sample consisting of physical disability individuals causes by accident or illness. There were six research participants involve in this research. The research method uses to collect the data are face-to-face interview, sound recording and journal writing by researcher. The face-to-face interviews take three sessions which were conducted in different date and different time. There are three main themes in this research. The themes are experiences, coping strategies in acceptance and coping strategies in adjustment. The finding shown each individual has different life experiences about their physical disability. In acceptance and adjustment themes, there are similarities and differences of coping strategies use among the physical disability adolescent (not natural born).